Performance of the main downstream operations on hyaluronic acid purification. (December 2020) - Cavalcanti, André Delano Domingos; Melo, Bruna Alice Gomes de; Ferreira, Bruno Armenio Moreira; Santana, Maria Helena Andrade
Highlights: An updated review of the hyaluronic acid purification processes. Review focusing on the main downstream operations. Precipitation is a common operation because of its benefits. High purity (over than 99 %) is required for clinical applications. This review aims to shed light on downstream operations to obtain HA for clinical uses. Abstract: Hyaluronic acid (HA), or hyaluronan, is a natural polyelectrolyte, ubiquitous in human tissues. Exogenous HA has been a valuable material due to its wide range of medical applications, such as in osteoarthritis treatment, ophthalmic surgery, adhesion prevention after surgeries and wound healing, as well as cosmetic applications. However, to ensure the physicochemical and biological properties, a purity near to 99 % is a primary requirement, aiming clinical applications. To achieve this goal, various downstream operations have been used, aiming HA concentration, separation and purification. Precipitation with organic solvents has been a common operation in most purification processes, combined with other downstream operations such as precipitation with quaternary salts, filtration, adsorption and ion exchange. This work presents an updated review of HA purification, emphasizing the performance of the main downstream operations used to achieve highly purified HA, in the period from 1970 to 2019. We conclude that, in the majority of the published works, there is a lack of studies regarding the operational conditions, as well as an absence of the purification percentage development during the processes.